Rethinking intergenerational knowledge transmission in the era of Industry 4.0 - Kuyken, Kerstin; Schropp, Rosanna (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2023)
Inspired by a human-centered perspective on technological changes of work, this paper presents a theoretical effort of bridging two distinct fields: Industry 4.0 and intergenerational knowledge transmission. It contributes to the literature on knowledge management with an analysis of how Industry 4.0, as one of the new objects of the 21st century management, challenges and transforms practices of intergenerational knowledge transmission. Based on a narrative literature review, we identify four facets representing the main managerial considerations on Industry 4.0, discuss their implications for intergenerational knowledge transmission and outline avenues for future research.